Polish agrarian structures in the 20-year perspective of the Common Agricultural Policy - Jeżyńska, Beata (Przegląd Prawa Rolnego, 2024)
Poland’s accession to the European Union in 2004 became an accelerator of transformation processes, especially the structural ones. The main transformation factor was the inflow of aid funds under the 2nd pillar of the Common Agricultural Policy. The legal analysis presented in the article covers the structural transformations in the perspective of the 20 years of the common agricultural policy in Poland. The main research objective was to assess the current legal state of its agrarian structures. The analysis led to the conclusion that generally the direction of changes in the structure of farms in Poland is consistent with that observed in countries with a higher level of agriculture. However, the pace of these transformations is too slow to expect a fast levelling out of the still existing differences, and resulting from it improvement of competitiveness. The changes that are desired in the area structure of farms in Poland require changes in the existing legal regulations. An urgent change is also needed in the regulation of agricultural leases and in the system of financing and allocating resources.